THE RELATIONSHIP BETWEEN EFFECTIVE TEACHER COMMUNICATION AND BULLYING BEHAVIOR OF CLASS X AND XI STUDENTS AT MUTIARA HIGH SCHOOL 17 AUGUST, BEKASI CITY, 2023 - Prayuda, Angga; Nurti Y.K. Gea; Riris Ocktryna (Rena Cipta Mandiri, 2023)
Background: Bullying is one of the serious problems in many countries, including Indonesia. Data recorded by KPAI from 2011 to 2019, bullying is still a dominating case of violence in the world of education. Bullying is an international problem that crosses lines of gender, economic status, culture, and race. Bullying is also a form of the most common violence in today's society, Bullying is described as deliberate, unwanted, aggressive repetitive behavior involving a real or perceived imbalance of power. Bullying is a public health problem that constantly impacts various aspects of life. Research Objective to determine the relationship between effective teacher communication and student bullying behavior at SMK Mutiara August 17, class X and XI Bekasi Bekasi in 2023. Research Method: This type of research uses quantitative research that aims to describe a phenomenon based on the data obtained. The design in this study uses Observational Analytics with a Cross sectional statistical approach. Cross Sectional approach is a study that aims to determine the relationship between two variables. Research Results: Based on the results of the Chi Square statistical test output with a 95% confidence level, a P Value of 0.003 was obtained. This shows that P Value (0.003 ) < α value (0.05). It can be concluded that Ha is accepted. Conclusion: There is a relationship between effective communication between teachers and bullies of grade x and XL students of SMK Mutiara August 17, Bekasi City in 2023.